Generative Literature: The Role of Artificial Intelligence in the Creative Writing Process - Prabowo, Bayu Ade; Asmarani, Rahmanti (Allure Journal, 2025)
This study explores the emerging phenomenon of AI-generated literature and its implications for creative writing, focusing on the characteristics of AI-generated texts, the impact of AI-human collaboration on the creative process, and the challenges posed by these technologies for traditional concepts of authorship, originality, and creativity. Through a comparative analysis of selected AI-generated literary works and a case study of the "Pharmako-AI" project, this research reveals the distinct stylistic, thematic, and structural features of AI-generated literature, as well as the complex dynamics of AI-human collaboration in the creative process. The findings suggest that while AI can serve as a powerful tool for creative exploration and experimentation, it also has limitations in terms of consistency, coherence, and emotional depth, and requires significant human input and judgment to shape the final literary output. The study contributes to the understanding of AI in creative writing by providing concrete insights into the capabilities and limitations of these technologies, and by highlighting the need for new frameworks and models to understand the nature of creative agency in the age of AI. The implications of AI-generated literature for the field of literature and future literary practices are discussed, including the potential for new forms of literary expression, new modes of authorship and collaboration, and new challenges to traditional concepts of originality and creativity. The study concludes with recommendations for future research, emphasizing the need for interdisciplinary collaboration and the development of new theoretical and methodological approaches to analyze and evaluate AI-generated literature.Â